2013
DOI: 10.2500/ajra.2013.27.3970
|View full text |Cite
|
Sign up to set email alerts
|

Standalone Balloon Dilation versus Sinus Surgery for Chronic Rhinosinusitis: A Prospective, Multicenter, Randomized, Controlled Trial

Abstract: Balloon dilation is noninferior to FESS for symptom improvement and superior to FESS for postoperative debridements in patients with maxillary and anterior ethmoid disease. Balloon dilation is an effective treatment in patients with uncomplicated CRS who meet the criteria for medically necessary FESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(113 citation statements)
references
References 27 publications
(35 reference statements)
2
105
0
6
Order By: Relevance
“…Results of the final study cohort of 135 patients in the REMODEL trial, with follow‐up from 1 to 2 years postprocedure, are consistent with the earlier reports from a smaller cohort of patients . Improvements in sinus symptoms after balloon dilation are maintained over a 2‐year time period and are similar to the improvements observed with FESS.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of the final study cohort of 135 patients in the REMODEL trial, with follow‐up from 1 to 2 years postprocedure, are consistent with the earlier reports from a smaller cohort of patients . Improvements in sinus symptoms after balloon dilation are maintained over a 2‐year time period and are similar to the improvements observed with FESS.…”
Section: Discussionsupporting
confidence: 84%
“…The REMODEL trial was a multicenter, randomized controlled trial comparing the outcomes of standalone balloon sinus dilation performed in the office setting versus standard FESS done in an operating room. The trial was statistically powered, with a minimum of 36 patients per arm needed to provide 90% power to detect a change of 0.8 in mean 20‐item Sino‐Nasal Outcomes Test (SNOT‐20) score . In total, 61 patients underwent treatment with FESS and 74 with balloon dilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutler et al [13] had a revision rate of 2.0% after 6-months follow-up, and Levine et al [19] had a rate of 5.8% after 1-year follow-up. Our revision rate of 14% needs to be established by other studies with equal follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of the procedure are the lack of knowledge of its long-term effect, the high costs of the disposable instruments, and its technical limitations in ethmoidal area or in removal of atypical mucosa [9]. Several uncontrolled and controlled studies have suggested balloon sinuplasty to be a safe and effective method [6,7,[10][11][12][13]. However, the limitations of these studies are the heterogeneity of patients and procedures as well as short follow-up time, which makes the conclusions difficult to draw.…”
Section: Introductionmentioning
confidence: 99%